Physical and Chemical Characteristics of Bio-Oil From Pyrolysis of Moringa Oleifera Seeds Using Microwave Technology - Abram Puspa Pramudita; samsudin anis; Wahyudi; Fitriyana, Deni Fajar; Halim, Sonika Maulana; Sukarni (Jurnal Bahan Alam Terbarukan, 2025)
This research aims to assess the potential of bio-oil from Moringa oleifera seeds through the analysis of physical and chemical characteristics resulting from the pyrolysis process. Raw materials in the form of Moringa oleifera seed powder were pyrolyzed at 400°C using a microwave reactor. To create oxygen free pyrolysis conditions, nitrogen gas was constantly flowed into the system at a rate of 0.15 NL/min. The process temperature was monitored using a K-type thermocouple, and the reaction was stopped when condensed vapor output was no longer observed. The pyrolysis products in the form of bio-oil and bio-char were then collected and weighed to determine the product fraction. Furthermore, the bio-oil was analyzed to determine its physical and chemical properties, including density, pH, and an indication of its constituent compound components. The results showed that pyrolysis under these conditions produced a dominant amount of bio-char (54.3%) and bio-oil of 24.7% of the total weight. The bio-oil obtained had a high density, in the range of 0.97-1.00 g/cm³, with a relatively acidic pH of 4.5-5.5. Although the bio-oil yield is not high, its complex chemical properties, particularly the content of phenolic compounds, nitriles, and amides, show great potential to be developed as a valuable bio-chemical base material such as antioxidants, biophenols, resins, and bioplastic raw materials. These findings strengthen the prospect of Moringa oleifera seeds as a strategic local biomass for sustainable bioindustry.